EFEKTIVITAS KONSUMSI DAUN KELOR (MORINGA OLEIFERA) TERHADAP KENAIKAN HEMOGLOBIN PADA IBU HAMIL DENGAN ANEMIA: SYSTEMATIC REVIEW - Anggie Pradana Putri; Yuniar Isyah Nurhidayah; Rina Tri Handayani (STIKES Pemkab Purworejo, 2024)
Background: Pregnancy can increase the risk of anemia due to higher iron requirements needed to support fetal growth and increased blood volume. Anemia in pregnant women can have serious consequences for both the mother and the fetus. One non-pharmacological intervention to address anemia in pregnant women is the consumption of Moringa oleifera leaves, which are rich in iron and other essential nutrients. Objective: This systematic review aims to analyze the effectiveness of consuming Moringa oleifera leaves in increasing hemoglobin levels in pregnant women with anemia. Methods: This study employs a systematic review method. Article searches were conducted in the Google Scholar and PubMed databases for publications from the past five years (2020-2024), using the PICO approach (Population: pregnant women; Intervention: Moringa oleifera leaves consumption; Comparator: no Moringa oleifera leaves, no anemia; Outcome: increased hemoglobin) for article selection. The article selection process adheres to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. The selected articles were then evaluated for quality using the Joanna Briggs Institute (JBI) Checklist. Results: The literature review of the selected articles showed a significant increase in hemoglobin levels in pregnant women after consuming Moringa oleifera leaves. The average increase in hemoglobin levels after the Moringa oleifera intervention ranged from 0.6 to 2 g/dL. Statistical tests in each study indicated a p-value <0.05, demonstrating statistical significance. Conclusion: The consumption of Moringa oleifera leaves has been proven effective in increasing hemoglobin levels in pregnant women with anemia. This intervention can be a safe and natural alternative to address anemia during pregnancy.